Role of SODC protein in antineoplastic drug resistance - Alamilla Presuel, Juan Carlos; González Vidal, Alejandro; Ruiz González, Óscar M.; Burgos-Molina, Antonio Manuel; Ruiz-Gómez, Miguel José (Aseica, 2022)
Cells need homeostasis to survive, therefore, they use the different pathways available to obtain it. The SODC protein overexpression, which is implicated in this process, suggests that could be implicated in the process of acquisition resistance during chemotherapy.
Keywords: Bioquímica; Inmunología; Ciencias; Fármacos; SODC protein; Fármacos antineoplásticos; Antineoplastic drug resistance